PERSPECTIVE OF A LEARNING COMMUNITY: MOVING TOWARDS A BLENDED LEARNING ENVIRONMENT IN A PRIVATE UNIVERSITY - PRAKASH, REKHA; SAMU, DAMAYA DEVI (Human Sustainability Procedia, 2018)
The purpose of this study is to analyse the engagementof satisfaction and motivation of a learning community with regard to extensive use of blended learning (BL). Blended Learning involves teaching techniques using technological tools and online materials to enliven classroom teaching. Instructors need to adaptthe methodology used in the classroom with the view of inculcating up to dateteaching pedagogy. The study is conducted among participants in a Teaching and Learning Course delivered using both face to face and blended formats. An analysis is made of instructors’ perception of a BL environment. The research group involves 10instructors from various departments who are under-going the Teaching and Learning Course.The results of the study could lead instructors to motivate students in their engagement and attitude towards a given taskby implementing BL in the subjects.This study would indicate that BL depends not only on the quality of the course and the virtual environment;it also involves using tools that could motivate students’ attitude towards a given task.